Oi, vy gusi! - Bobrova, Lidia (Soviet Union : Lenfilm, 1991)
Director Lidia Bobrova wanted to tell the astonishingly bleak story of her brothers' lives and kept resubmitting this movie project to the state film boards for approval. Finally, after ten years, she was allowed to shoot it. The backbone of the story is the daily life of brother Mitka, whose health is so poor he is not allowed to work. Instead, his wife Raya supports them as a seamstress, despite her heart condition. Nearby lives brother Petka, another impecunious man, who is amusingly tiny when compared to his strong, solid wife: she earns their living as a nurse in a retirement home. Brother Samya has been in a prison camp for committing murder, and he is only now returning home to join his other brothers.
Duration: 01:23:00
Keywords: Fiction films